2022
DOI: 10.3390/healthcare10101981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Augmented Reality Game-Based Cognitive–Motor Training on Restricted and Repetitive Behaviors and Executive Function in Patients with Autism Spectrum Disorder

Abstract: Restricted and repetitive behaviors (RRBs) and executive dysfunction are widely acknowledged as core features and hallmarks in patients with autism spectrum disorder (ASD). This study aimed to investigate the effects of augmented reality (AR) using motivational games with cognitive–motor exercises on RRBs, executive function (EF), attention, and reaction time in patients with ASD. Twenty-four patients (range from 6 to 18 years) diagnosed with ASD were recruited from local social welfare centers and randomly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Its main objective is to review and synthesize the ndings of recent experimental exergaming studies. Eleven studies met the inclusion criteria and were included in our nal analysis [20,21,[26][27][28][29][30][31][32][33][34]. Overall, our data suggested that exergaming interventions could signi cantly improve executive functions (e.g., cognitive exibility, inhibition control, and working memory) in healthy and special children aged 4-12 years old.…”
Section: Discussionmentioning
confidence: 96%
“…Its main objective is to review and synthesize the ndings of recent experimental exergaming studies. Eleven studies met the inclusion criteria and were included in our nal analysis [20,21,[26][27][28][29][30][31][32][33][34]. Overall, our data suggested that exergaming interventions could signi cantly improve executive functions (e.g., cognitive exibility, inhibition control, and working memory) in healthy and special children aged 4-12 years old.…”
Section: Discussionmentioning
confidence: 96%
“…Irrespective of this there are several reasons this might arise. For example, the greater risk could be associated with motor difficulties in ASD including weak neuromuscular interaction (Nadeem et al, 2021) or the restricted and repeated behaviors that can arise (Nekar et al, 2022), which may increase the risk of overuse injury. Recent research has indicated that individuals with ASD also often show symptoms of hypermobility (Nisticò et al, 2022), although it is unclear that being hypermobile increases risk of overuse injury (De Smet et al, 1998; Junge et al, 2015).…”
Section: Discussionmentioning
confidence: 99%